Customized Allogeneic Bone Augmentation Improves Esthetic Outcome in Anteromaxillary Dental Implantation - Manfred Nilius; Minou Hélène Nilius; Charlotte Mueller; Bernhard Weiland; Dominik Haim; Anna Krahe; Guenter Lauer (Case Reports in Dentistry)
Purpose. In cases of severe atrophic maxilla or maxillary involution, augmentation is necessary for implant-supported prosthetics. Using bone grafts is a standard procedure, and using customized allogeneic bone blocks may be a predictable alternative before dental implantation. Clinical Findings. This case study shows the digital workflow, including a preimplantological augmentation by a customized allogeneic block, followed by soft tissue optimization and template-based dental implantation, after six months of healing. It is part of a three-year follow-up study on the resorption rate of allogeneic bone blocks. Outcomes. Allogeneic bone augmentation is an alternative treatment option to autologous bone grafts. It allows predictable advanced backward planning (ABP) even in the maxillary esthetic zone. Diameter-reduced implants show long-term stability of a minimum of three years after loading and excellent results of prosthetic fixtures. Conclusion. Prefabricated customized allogeneic blocks for augmentation may increase the fitting accuracy of the graft, decrease morbidity, and reduce the operation time in esthetic maxillary rehabilitation.